Effect of Pyrolean acid on the germination of Sandia, Cocona and Cacao in the District of San Gabán, Carabaya - Pelinco Ruelas, Edgar (2020)
For the present research work, the main objective was to evaluate the effect of pyrolenous acid and the optimal dose for the germination of watermelon, cocona and cacao seeds; the randomized complete design statistical model was used, the factors under study were: pyrolenous acid dose obtained from Bambú, Pisonay and Cético (1, 10, 100 ml) and seeds of the three mentioned species, we worked with 9 treatments and a control plus three repetitions, the variables were: germination percentage and dose. The results indicate significant effects of pyrolenous acid on germination, of cocona seeds, cacao with 96.70%, and 100%, however, there were negative effects for watermelon seeds. Likewise, the application of pyrolenous acid at a dose of 10 ml had the best results in the germination of cacao and cocona seeds with 97% and 90%. In conclusion, the application of pyrolenous acid at doses of 10 ml improved the germination process of the Cocona and Cacao seeds, however, at a high dose of 100 ml it inhibits germination, finally, the 1 ml dose does not show positive effects respectively.